Eficiencia del gasto público del Gobierno Regional de Loreto y su influencia en las necesidades básicas en la región Loreto 2014 - 2021 - Mori Pinedo, Jhon Paul (2023)
The objective of this research work is to determine if the efficiency of public spending of the Regional Government of Loreto positively influences the satisfaction of basic needs in Loreto in the period 2014-2021; because the correct use of public resources administered by decentralized governments contributes to closing the social, economic, educational, health and housing gaps. The research was of a quantitative type, correlational-causal level and non-experimental design with longitudinal data, which included as study population all the statistical data of the public budget of the Regional Government of Loreto, and the five dimensions of the basic needs of the inhabitants of the homes of the Loreto region. Applying the linear regression model using the OLS method at the 90% confidence level, it was determined that the efficiency of public spending by the Loreto Regional Government does not influence the satisfaction of basic needs in Loreto because the individual significance test exceeds the 10% significance level. Therefore, there is no relationship between the variables.